PROGRAM SEKOLAH LITERASI GRATIS (SLG) DI STKIP PGRI PONOROGO - Nafi’ Mukharomah (ABDAU : Jurnal Pendidikan Madrasah Ibtidaiyah, 2018)
This article aims to explore the implementation of the Free Literacy School (SLG) program at STKIP PGRI Ponorogo. This type of research is qualitative descriptive research. The location of the study took place at STKIP PGRI Ponorogo, address on Jalan Ukel number 39 Kertosari Babadan Ponorogo East Java province. The research subjects were participants who had attended the Free Literacy School (SLG). The research instrument used was interviews and documentation. The results of the study show that the implementation of the Free Literacy School (SLG) program received a tremendous response from participants living in Ponorogo and its surroundings. The efforts made by the committee in implementing the Free Literacy School (SLG) program are: (1) presenting a number of practitioners and academics from various regions who are experts in their respective fields, (2) the entry into force of attendance requirements for participants who take the Free Literacy School ( SLG), (3) arranging topics on literacy materials, and (4) giving certificates of appreciation to participants who meet the criteria. Therefore , the implementation of the School of Literacy Literacy (SLG) program needs to be continued for the following years which will certainly develop in other institutions and regions. Considering the noble purpose of this Free Literacy School is to make the young generation who are literate and literate.